2019
DOI: 10.1021/acs.jafc.8b05447
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Myricetin as a Potent Inhibitor of Human Flap Endonuclease 1, Which Potentially Can Be Used as Sensitizing Agent against HT-29 Human Colon Cancer Cells

Abstract: Human flap endonuclease 1 (hFEN1) is instrumental in DNA replication and repair. It is able to cleave the 5′ single-stranded protrusion (also known as 5′ flap) resulting from strand displacement reactions. In light of its crucial functions, hFEN1 is now deemed as a nontrivial target in the DNA damage response system for anticancer drug development. Herein, we report that myricetin and some natural flavonoids are able to inhibit hFEN1. Structure–activity relationship, inhibitory mechanisms, molecular docking, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…This study suggested that myricetin can be utilized for the design of therapeutic agents against human colon cancer. Myricetin also acts as a potent inhibitor of human flap endonuclease 1 (hFEN1) protein (IC 50 690 nM), based on inhibitory mechanisms, molecular docking, and cancer cell-based assays [128]. The hFEN1 protein is a functional member of the 5′-nuclease superfamily.…”
Section: Parkinson Diseasementioning
confidence: 99%
“…This study suggested that myricetin can be utilized for the design of therapeutic agents against human colon cancer. Myricetin also acts as a potent inhibitor of human flap endonuclease 1 (hFEN1) protein (IC 50 690 nM), based on inhibitory mechanisms, molecular docking, and cancer cell-based assays [128]. The hFEN1 protein is a functional member of the 5′-nuclease superfamily.…”
Section: Parkinson Diseasementioning
confidence: 99%
“…8 Moreover, FEN1 is considered a marker for metastasis and poor prognosis in multiple cancers; [9][10][11] additionally, recent studies have revealed that FEN1 has a role in regulating sensitivity to chemotherapy. 12,13 Autophagy is a stress-relieving/homeostatic cellular recycling process involved in the maintenance of cellular homeostasis through the lysosomal degradation of various proteins and damaged organelles. 14 Accumulating evidence has shown that autophagy can promote survival in patients undergoing chemotherapy, radiotherapy, and targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Among them, DNA damage repair is a new and important mechanism of tumor drug resistance and it is also a hottopic at present. Recent studies have shown that the BER activity as an important pathway of DNA damage repair is related to the chemotherapy sensitivity, and the studies of FEN1 have been widely concerne d [23][24][25]. Multiple studies have demonstrated that high FEN1 expression is associated with drug resistance in a variety of malignancies.…”
Section: Discussionmentioning
confidence: 99%